ASEAN economic structure and changes in agricultural protection - David, Cristina C. (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1989)
This paper analyzes changes in the economic structure as well as agricultural protection for four ASEAN countries - Indonesia, Malaysia, Philippines, and Thailand- from 1960 to 1982. The cause of change in agricultural protection are examined to infer the varying trends of the comparative advantage in agriculture. It compares the intersectoral pattern of protection and exchange rate policies to evaluate how much each country's economic policies have hindered or promoted agriculture's comparative advantage. Although the relative importance of the agricultural sector is seen to be declining in the ASEAN countries studied, the trends in nominal protection rates do not clearly indicate when the switch from taxing to subsidizing agriculture observed in the process of economic development will occur.